2012
DOI: 10.1037/a0025985
|View full text |Cite
|
Sign up to set email alerts
|

The attentional blink is not affected by backward masking of T2, T2-mask SOA, or level of T2 impoverishment.

Abstract: Identification of the second of two targets (T2) is impaired when presented shortly after the first (T1). This attentional blink (AB) is thought to arise from a delay in T2 processing during which T2 is vulnerable to masking. Conventional studies have measured T2 accuracy which is constrained by the 100% ceiling. We avoided this problem by using a dynamic threshold-tracking procedure that is inherently free from ceiling constraints. In two experiments we examined how AB magnitude is affected by three masking-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 34 publications
3
9
0
Order By: Relevance
“…False-discovery rate (Benjamini & Hochberg, 1995) corrected t tests indicated that Lag effects were absent on T2 in two-target trials, t < 1, whereas T3 report was worse at lag 3 relative to lag 9 in three-target trials, t(1, 39) = 18.6, p < .001, that is, a small but reliable AB effect was detected in spite of the absence of a distractor trailing T3. These findings converge with prior studies reporting small but reliable AB effects even when the last target is not masked by trailing distractors (Jannati et al, 2011(Jannati et al, , 2012Ptito et al, 2008;Sessa et al, 2007;Giesbrecht & Di Lollo, 1998).…”
Section: Behaviorsupporting
confidence: 34%
See 1 more Smart Citation
“…False-discovery rate (Benjamini & Hochberg, 1995) corrected t tests indicated that Lag effects were absent on T2 in two-target trials, t < 1, whereas T3 report was worse at lag 3 relative to lag 9 in three-target trials, t(1, 39) = 18.6, p < .001, that is, a small but reliable AB effect was detected in spite of the absence of a distractor trailing T3. These findings converge with prior studies reporting small but reliable AB effects even when the last target is not masked by trailing distractors (Jannati et al, 2011(Jannati et al, , 2012Ptito et al, 2008;Sessa et al, 2007;Giesbrecht & Di Lollo, 1998).…”
Section: Behaviorsupporting
confidence: 34%
“…First, the last target embedded in RSVP was not trailed by distractors so as to allow us to observe fully fledged P3b and P3a responses to this stimulus. Little or no behavioral AB is typically observed for unmasked targets (e.g., Jannati, Spalek, Lagroix, & Di Lollo, 2012;Jannati, Spalek, & Di Lollo, 2011;Ptito et al, 2008;Sessa et al, 2007;Giesbrecht & Di Lollo, 1998). However, under these conditions, the underlying neural process evoked by T1 that produces the behavioral AB for a masked T2 should still occur, and it is this underlying neural process that is the subject of our inquiry.…”
Section: Introductionmentioning
confidence: 99%
“…Lag effects, though of different magnitude, were detected both when the mask was present, t(33) = 10.99, MSE = 0.024, p < 0.0001, and when the mask was absent, t(33) = 3.01, MSE = 0.010, p = 0.005. Results indicated that, in the absence of a mask, an AB effect was only found for T1-present trials, converging with prior studies (Dell'Acqua et al, 2015;Giesbrecht & Di Lollo, 1998;Jannati, Spalek, & Di Lollo, 2010, 2012Sessa et al, 2007). As expected, in mask-present trials the AB deficit (lower accuracy for lag 3 trials vs. lag 8) was more pronounced when more targets were presented (T1-present vs. T1-absent) t(33) = 7.37, MSE = 0.0193, p < 0.001.…”
Section: Behavioralsupporting
confidence: 88%
“…K was estimated by means of the change-detection paradigm outlined above. Rate of encoding was estimated with a variant of the backward-masking paradigm that has been used extensively to curtail the time available for target processing (e.g., Kolers, 1968;Michaels & Turvey, 1979;Spencer & Shuntich, 1970). In those studies, the time available for processing one or more letters was curtailed by the onset of a temporally trailing pattern mask.…”
Section: Methodsmentioning
confidence: 99%